Germination of Vernonia ferruginea as a function of breaking dormancy, light and temperature - Yamashita, Oscar Mitsuo; Alberguini, Alcione Lidiane (Comunicata Scientiae, 2011)
The understanding of basic information on biology of weeds can contribute significantly to the construction of appropriate strategies for their management, and enable the development of tools for non-chemical control. The aim of this work was to study the effect of breaking dormancy, of light and of temperature on germination of Vernonia ferruginea seeds. The experiments were developed in the seed laboratory of the University of Mato Grosso State. In the first experiment, we studied 5 methods of breaking dormancy: control, sandpaper, sulfuric acid, GA 3 and KNO3. None of the treatments showed higher germination than the control; the use ofsulfuric acid and sandpaper significantly reduced the number of seeds germinated. In the second experiment, under different lighting conditions (and without it) and temperature (25 ºC, 25/30 ºC and on bench), it was observed that the species is photoblastic positive, with higher germination on laboratory bench.